Developing Vegetables Card Media As A Learning Media For Elementary School Students - Dina Fadhilah; Theresia Ninuk Sri Hartini; I Made Alit Gunawan; Ayu Triani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
Nutrition education efforts in schools have a great opportunity to successfully improve the knowledge of nutrition among the community because school students are expected to be a bridge for teachers with their parents, teachers as educators in the teaching and learning process have an influence on their students who are sometimes more comply than parents. Nutrition education should be given as early as possible, because children generally have a high desire to know and learn something further. The appropriate age of children to be given nutritional education is at 6-14 years, because this is the intellectual period in which children begin to learn. From the range, the most appropriate time in giving nutritional counseling is at the age of 11 years because at that age children are in the formal operational stage, which means able to think in abstract, build logical reasoning, and draw the conclusions of available information. The right media will increase the spirit of self-study according to the environment and enable students to learn by themselves according to their interests and abilities. Media must be created by not ruling out good and correct media requirements, so that information can be received in accordance with the wishes of the messenger. This research is a media development research. Starting by designing the format of the form and the content of the media. Furthermore the card was validated by 2 media experts, those were a lecturer in Health Polytechnic of Ministry of Health in Yogyakarta and a graphic designer. Then it was tested to 20 students of class V of academic year 2016/2017 in SDN Nglahar 1, Yogyakarta. Methods of data collection using questionnaire method and analyzed. The results concluded that vegetables cards developed were feasible to use. Presentation of feasibility based on validation result from lecturer and graphic design was 80.32% (feasible) as well as response from elementary school student equaled to 80.74% (feasible).